Post-Voltage-Boost Circuit-Supported Single-Ended Class-B Amplifier for Piezoelectric Transducer Applications - Kim, Jungsuk (Sensors (Basel), 2020)
Piezoelectric transducers are important devices that are triggered by amplifier circuits in mobile ultrasound systems. Therefore, amplifier performance is vital because it determines the acoustic piezoelectric transducer performances. Particularly, mobile ultrasound applications have strict battery performance and current consumption requirements; hence, amplifier devices should exhibit good efficiency because the direct current (DC) voltage in the battery are provided to the supply voltages of the amplifier, thus limiting the maximum DC drain voltages of the main transistors in the amplifier. The maximum DC drain voltages are related with maximum output power if the choke inductor in the amplifier is used. Therefore, a need to improve the amplifier performance of piezoelectric transducers exists for mobile ultrasound applications. In this study, a post-voltage-boost circuit-supported class-B amplifier used for mobile ultrasound applications was developed to increase the acoustic performance of piezoelectric transducers. The measured voltage of the post-voltage-boost circuit-supported class-B amplifier (62 V(P-P)) is higher than that of only a class-B amplifier (50 V(P-P)) at 15 MHz and 100 mV(P-P) input. By performing the pulse-echo measurement test, the echo signal with the post-voltage-boost circuit-supported class-B amplifier (10.39 mV(P-P)) was also noted to be higher than that with only a class-B amplifier (6.15 mV(P-P)). Therefore, this designed post-voltage-boost circuit can help improve the acoustic amplitude of piezoelectric transducers used for mobile ultrasound applications.